Association Between Cardiovascular Risk and Depressive Symptoms Among People With Serious Mental Illness. Issue 8 (August 2017) - Naslund, John A.; Aschbrenner, Kelly A.; Pratt, Sarah I.; Lohman, Matthew C.; Scherer, Emily A.; McHugo, Gregory J.; Marsch, Lisa A.; Unützer, Jürgen; Bartels, Stephen J.
Abstract : Abstract: Depressive symptoms have debilitating effects on the physical health and functioning of people with serious mental illness. We examined change in depressive symptoms among overweight and obese adults with serious mental illness ( n = 343) using data combined from two randomized trials comparing the 12-month In SHAPE program to a gym membership control condition. In SHAPE consists of a gym membership, weekly individual meetings with a fitness trainer, and instruction on healthy eating and nutrition. Depressive symptoms were measured at baseline, 3, 6, and 12 months. Change in depressive symptoms did not differ between groups, but depressive symptoms decreased over time across the entire sample ( p = 0.045). At 12 months, reduced depressive symptoms were associated with clinically significant improved cardiorespiratory fitness ( p = 0.030), 10% or more weight loss ( p = 0.044), and cardiovascular risk reduction ( p = 0.028) across both groups. Our findings suggest that participation in health promotion programs resulting in cardiovascular risk reduction may be associated with reduced depressive symptoms.